Neo-patrimonial practices and sustainability of authoritarian regimes in Eurasia. Issue 2 (June 2019) - Shkel, Stanislav N.
Abstract: The article analyzes authoritarian regimes within the post-Soviet territory in terms of informal practices (clannishness, clientelism and patronage) and their characteristics used by political leaders to form a power coalition. It has been argued that any of these informal practices determine a power coalition of a certain size, which is consequential for regime sustainability. Power coalitions formed on the basis of a clan-like nature is the least effective way to retain power and generally leads to regime destabilization. Clientelism, which allows for forming a power coalition on a wider basis, is a more effective strategy in terms of regime sustainability. Maximum regime sustainability is reached when patronage practices are used, which require more material resources and are only accessible to a limited number of wealthy states.